Change in Nasal Airflow, Associated with the Treatment of Rapid Maxillary Expansion in Children with Maxillary Compression - Torre Martínez, Hilda Hortencia Hermelinda; Zertuche de la Fuente, Alejandra; Carrillo González, Roberto José; Theriot Girón, María del Carmen; González Díaz, Sandra Nora; Arias Cruz, Alfredo (Crimson Publishers, 2019)
Purpose: To determine the change of nasal airflow (ANF) in children with maxillary compression after performing rapid expansion treatment. Materials and methods: The sample consisted of 30 patients who attended the Orthodontics Postgraduate Program of the Autonomous University of Nuevo Leon (UANL). They underwent clinical history, study models, lateral cephalogram and orthopantomography. Those who presented maxillary compression were referred to the Regional Center of Allergy and Clinical Immunology (CRAIC) of the University Hospital, UANL., Where a rhinomanometry (T1) was performed to know the values of nasal airflow (NAD) and nasal resistance (RN). before starting the maxillary expansion treatment (ERM). ERM was performed with a Hyrax type expansion screw. Three subsequent registrations were performed with rhinomanometry, the first was one month after starting the ERM (T2), the second to the third month (T3) and the third to the ninth month (T4). Changes in the nasal airflow were compared after of the maxillary rapid expansion, with the student’s t test, with p≤0.05, for related samples. Results: The values of the FAN increased as the measurements were made, on the other hand, the RN decreased progressively. The results were not statistically significant from one time to another. We did not find a statistically significant difference in relation to gender, nor to the present symptomatology. The group of 9 to 10 years was especially favored in relation to the two groups of greater age. Conclusion: The treatment of MRS is an effective treatment to relieve maxillary compression, helps improve nasal capacity, increasing FAN and decreasing the NR; however, it is not recommended in order to improve nasal permeability exclusively.